Turnaround Strategies and External Weaknesses: Analysis of Case Studies - Elhezzani, Nawaf (2017)
The core aim of this paper was to study the various turnaround strategies that companies employ. Among the issues that the paper touched on include the various challenges that businesses face and which could necessitate a turnaround, the role of management in transforming the fortunes of organizations, the resources used, and the changes that an organization may implement as part of its turnaround strategy. The study utilized a descriptive methodology to collect and analyze the data. Specifically, the case study method was employed to meet the data needs. The companies selected for this research were Ford, Chrysler, Tesco, and Netflix. While carrying out the study, the researcher was keen to analyze the factors that led each organization needing a turnaround as well as what was done to change the fortunes of the company. The findings revealed that different companies have varied approaches to turnarounds. Some of them such as Tesco and Ford brought in new leaders to steer them through the transformation. In doing so, they believe that they will benefit from an infusion of new ideas and perspectives as they look to turn their fortunes. In other instances, an organization may opt to radically change its business model as was the case with Netflix. Further, some carry out a reorganization of the firm’s assets and resources to focus on the areas that will lead to sustained profitability. Such was the case with Ford that chose to focus on making cars that responded to the market needs at the time and Tesco that chose to freeze its planned branch extension. Therefore, there are many different approaches towards an organizational turnaround strategy.